The Importance of Interprofessional Education for Students in Communication Sciences and Disorders. (February 2015) - Goldberg, Lynette R.
Interprofessional education (IPE) is recognized as a critical component in preparing students for effective interprofessional practice in health care. IPE is supported by the American Speech-Language-Hearing Association and students' competence in interprofessional practice is expected by clinical supervisors for effective work in any setting, whether that setting is medically or educationally oriented. IPE thus needs to be integrated into the curriculum of academic programs in Communication Sciences and Disorders and supported by clinicians in the field. This short tutorial is designed to acquaint readers with the concept of IPE, the collaborative competencies that students develop, available learning models, the importance of measuring the effectiveness of any interprofessional intervention, and ongoing challenges that need to be addressed to facilitate the implementation of this valuable learning strategy.